Characteristics of spatiotemporal distribution of HIV-1 Gag-containing complexes on the dorsal membrane tracking with live confocal imaging - Xiao Wang; Xinye An; Hongmei Zhao; Dakang Sun (PLoS ONE, 2025)
Introduction In recent years, novel detection methods have provided significant insights into the real-time morphological changes occurring during the HIV life cycle within host cells. However, the detailed dynamics of virus assembly and release, particularly from the perspective of the dorsal cell membrane, remain poorly understood. Methods HEK293T cells were transfected with pEGFP-N3-Gag plasmids, and the spatiotemporal distribution of Gag-EGFP was monitored using the “xyt” or “xyz” imaging modes of laser confocal microscopy (LCM). The motion trajectory of GCC in living cells was manually tracked using the MtrackJ plugin in ImageJ 1.54p. 3D reconstruction of target proteins were processed with the Volume Viewer plugin in ImageJ 1.54p. Results The results revealed that Gag-EGFP proteins exhibited directional movement toward the plasma membrane, where they assembled into Gag-containing complexes (GCCs) of varying sizes and displayed localized small-scale displacements. Furthermore, GCCs on the cell membrane were observed to detach from the dorsal membrane and were subsequently released into the extracellular environment within 3–8 minutes. Three-dimensional (3D) reconstruction demonstrated that Gag-EGFP proteins exist in three distinct forms: granule-like structures, cord-like structures, and giant polymers on the dorsal membrane or in the cytoplasm. Conclusion Overexpressed Gag proteins on the dorsal cell membrane can form dynamic polymers of various sizes that undergo localized movement or detach from the membrane at different rates. The small spots of GCCs observed in a single confocal plane may actually have significantly larger sizes and unexpected shapes within the cell.